Different effects of social capital on health status among residents: evidence from modern Japan - Eiji Yamamura (Economics and Econometrics Research Institute (EERI), 2010)
This paper aims to explore how social capital is related to self-rated health status in Japan and how this relationship depends on the extent to which a person is embedded into the community. This study used data from 3079 adult participants in Japan's Social Policy and Social Consciousness (SPSC) survey conducted in 2000. Controlling for unobserved city size- and area-specific fixed effects, I find through Ordered Probit estimations that social capital has a significantly positive effect on health status for long-time but not for short-time residents. Results also suggested that the experience of divorce is negatively associated with health status for long- time but not short-time residents. People can enjoy a social network, a kind of social capital, if they are a member of such a network. Nevertheless, people appear to be negatively influenced if they are excluded from networks. Such positive and negative effects of social capital are more obvious when people are more deeply integrated into a community. Empirical study provided evidence that social capital and socio-economic effects on health status are significantly influenced by the extent to which respondents are integrated into a community.
Keywords: I19; Z13; R58; 330; Social capital; health status